Post-tension column for IBS blockwork building system - Ayop, Zalilah (2013)
Industrialized Building System (IBS) is now a common remark in construction industry. The used of this system have grown rapidly around develop country including Malaysia. This research is mainly focused on the interlocking blockwork system for the residential building house. The concrete blocks were assembled by stacking up and jointed together, by the bolt only without the interlocking void in the blocks. The assembly of beam and column are by bolts only. This study focuses on the pretension bolt at the column only. The stress value at the bolt is needed in order to apply pretension or preloading to the bolt. The purpose of this study is to investigate the behaviour of the frame structure of the blockwork system under point loads in both experimental which is constructed in the laboratory and analysis of the structure modeled in finite element analysis software (Abaqus/CAE). The behaviour of the structure observed during the testing was merely the pattern of the crack occurred when the frame is loaded. Based on the analysis that has been performed, the residual stress in the bolt is determined and the actual pretension bolt value in the column is calculated which gives 0.251 kN, while the torque that need to be applied at the nut is 0.102 kNmm